Asian Transformations An Inquiry into the Development of Nations - Nayyar, Deepak (Oxford University Press, 2019)
Gunnar Myrdal published his magnum opus, Asian Drama: An Inquiry into the Poverty of Nations, in 1968. He was deeply pessimistic about development prospects in Asia. The fifty years since then have witnessed a remarkable social and economic transformation in Asia - even if it has been uneven across countries and unequal between people - that would have been difficult to imagine, let alone predict at the time. This book analyses the fascinating story of economic development in Asia spanning half a century. The study is divided into three parts. The first part sets the stage by discussing the contribution of Gunnar Myrdal, the author, and Asian Drama, the book, to the debate on development then and now, and by providing a long-term historical perspective on Asia in the world. The second part comprises cross-country thematic studies on governments, economic openness, agricultural transformation, industrialization, macroeconomics, poverty and inequality, education and health, employment and unemployment, institutions and nationalisms, analysing processes of change while recognizing the diversity in paths and outcomes. The third part is constituted by country-studies on China, India, Indonesia and Vietnam, and sub-region studies on East Asia, Southeast Asia and South Asia, highlighting turning points in economic performance and analysing factors underlying success or failure. This book, with in-depth studies by eminent economists and social scientists, is the first to examine the phenomenal changes which are transforming economies in Asia and shifting the balance of economic power in the world, while reflecting on the future prospects in Asia over the next twenty-five years. It is a must-read.